Payroll accounting information system at PT. Telekomunikasi Indonesia Tbk - M Firman (LPPM Politeknik Jambi, 2019)
Purpose - the purpose of the payroll accounting information system is to be able to process data quickly and precisely, making it easier for the admin section in the payroll process and can improve employee performance efficiently. Design / Methodology / approach - Payroll information system that the writer built at PT. Mega Pratama Insurance uses a web-based information system. The system development method in the study uses the waterfall model and the data flow model used is, DFD (Data Flow Diagram). The design of this system is assisted by several tools such as XAMPP version 3.2.1, Notepad ++ web editor, Adobe Dreamweaver web and Mozilla Firefox web browser. Findings - The author chose this company because the payroll system in this company is still done manually, using Microsoft Word and Microsoft Excel. The variable used in this study is the payroll information system at PT. Mega Pratama Insurance. Originality/value - Payroll information system at PT. Mega Pratama Insurance uses three user access rights, namely, user as admin, user as employee and user as manager.